Organizational routines in Russian companies: Review of practices - Valieva, Olga Vladimirovna (Serbian Journal of Management, 2014)
Results of the first stage of the researches conducted in 2012-2013 are presented in the article. Researches are connected with studying of transformational processes intra corporate administrative the practices in the Russian companies and their subsequent institutionalization. Preliminary results showed that depending on time of existence of the enterprise the practices connected with adaptation of the enterprise to environmental conditions change only. Intra corporate forms of interaction thus remain invariable. The factorial analysis revealed six types of the routines influencing activity of the companies. The analysis showed the importance of adaptive type of organizational structures in management and functioning of the companies, progressive methods of processing of information flows, and also the principles of group decision-making and the power of the founder in Russian companies.